Contraceptive practices among reproductive age group of women in Justice K. S. Hegde Medical College Hospital, Mangalore - Manjeera M, Lakshmi; ., Neetha; Rai, Supriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: India’s population as per 2011 census was 1.21 billion second only to china in the world, and is estimated to overtake china by 2050. India was the first country to launch National Family Planning Program in 1952. Even though various measures have been taken to encourage the usage of contraception but, the achievement in this field was not to the extent expected due to various social and cultural factors. Methods: It was a cross sectional study conducted in out patients and inpatients of department of obstetrics and gynecology, Justice K. S. Hegde medical college hospital, Mangalore. The study constituted 705 subjects. It was an interview based study. The study was aimed to know the awareness, acceptance and prevalence of temporary and permanent contraceptive methods among the study group and various factors affecting the contraceptive usage. Results: A total of 705 women in the age group between 18-45 years were studied. 671 (95.2%) were aware of one or multiple methods of contraception, 615 (87.2 %) accepted the contraceptive practices, and 495 (71.2%) followed or are following contraception at the time of study. Of 705 women, 366 (51.9%) followed or used temporary methods, 227 (32.2%) followed permanent methods of contraception. Conclusions: Awareness about the contraception is not sufficient enough to use contraception in the community, also shows that more programs are required to combat the influence of various factors on contraception usage, and emphasizing on the positive effects of the use of contraception.